Vibration training: benefits and risks - Mester, J.; Kleinöder, H.; Yue, Z. (Journal of Biomechanics, 2006)
The main results of our recent several studies, i.e. the measurements of vibration training results for single case and group studies as well as the cardiovascular parameter measurements during vibrations and the corresponding hydrodynamic analysis, are summarized. Our studies and previous work all confirm that vibration training is an effective training method in order to improve maximal strength and flexibility as well as various other factors if the training is properly designed. Some recommendations regarding the proper ranges of frequencies, amplitudes and exposure duration of vibration training are made based on the existing vibration training practice and mechanism analysis, although much work remains to be carried out in order to set up clear rules for various groups of people so that maximal training results could be expected and in the meantime potential dangerous effects could be avoided.